Socio-Geospatial Characteristic of Communities Affected by Contemporary Hydrometeorological Disaster During The Covid-19 Pandemic in Cimanggung Sub-District, Sumedang District, West Java Province - Wilopo, Wilopo; Puspasari, Poetika; Sutisna, Sobar; Maarif, Syamsul; Widana, I Dewa Ketut Kerta (Technium Social Sciences Journal, 2022)
Hydrometeorological disasters has dominated the list of disasters in Indonesia in recent years. Cimanggung Sub-District in Sumedang District which located in West Java Province is one of the areas experiencing hydrometeorological disasters, namely landslides and floods in January 2021. This disaster event is an example of an interesting phenomenon to conduct innovative research in the context of disaster management that occurred in the Covid-19 pandemic era. Thus, this research aims to analyze the socio-geospatial characteristics of the affected community so that it can explore the level of survival capacity of the community affected by the contemporary hydrometeorological disaster through the identification of its socio-geospatial characteristics in Cimanggung Sub-District, Sumedang District. This study uses an exploratory survey method for social and geospatial parameters and will be analyzed quantitative qualitative sequential with the GIS-Overlay technique based on observation data and field surveys and the results of interviews with affected communities. The results showed that: 1). The characteristics possessed by the people of Cimanggung Sub-District and the landslide disaster during the Covid-19 pandemic that occurred influenced each other both positively and negatively; 2). Geospatial characteristics in Cimanggung Sub-District basically place the local community's livelihood at risk of landslide hazard; and 3). Landslides and floods during the Covid-19 pandemic that occurred in Cimanggung Sub-Distruct had a domino impact on the community which greatly affected the dimensions of human security. Morphological conditions affect the characteristics of people who have community attachment to fellow communities and their environment. However, this characteristic is also an obstacle in the housing relocation process that will be carried out by the government. On the other hand, the community attachment has the nature of mutual cooperation helps the disaster emergency response process so that it is carried out more effectively.